Quitandas quilombolas: identidades, resistência e etnodesenvolvimento em paisagens culturais do Médio Jequitinhonha - Luciana Priscila do Carmo (2019)
This dissertation deals with the studies of Cultural and Human Geography, highlighting the traditional foods (‘Quitandas’) production and the know-how as practices of social and cultural reproduction of Maroons’ communities (Quilombolas) of the region located in the Middle Jequitinhonha Valley - northeast of Minas Gerais state- eastern Brazil, and more specifically of communities located in the municipalities of Chapada do Norte and Berilo. The general objective of this work was to investigate to what extent there would be a recognition of the ‘Quitandas’ by ‘Marrons’ groups as elements of their cultural and collective identity. From this, it was tried to understand if a possible identification and valorization of cultural landscapes could be a factor that contributes / justifies, or not, with / for actions / measures of protection, safeguard and / or seal of material, immaterial and landscape patrimony, besides of strengthening an Ethnodevelopment processes of ‘Quilombolas’ and ‘traditional communities’ in the Middle Jequitinhonha. The studies are being carried out through a Etnogeographic Method, closely linked to the categories of analysis and qualitative paradigms of interpretation of Cultural Geography, with elements and/ or approaches with Ethnography, influenced by marxism philosophical and theoretical-methodological reflections in its cultural aspect and of complexity theory, to study the production and means of production of the ‘Quitandas’. The protagonism assumed, in the process, by black women (that is Maroon women family farmers)- that guarantee these actors’ social and cultural reproduction–, is what impressed the greater continuity of family groups in the rural environment and favored their cultural permanence in ‘Quilombolas’ territory in Jequitinhonha Valley. Different relationships established between these women and traditional foods know-how and the broader dimensions of the I’ identitybuilding and reconstruction process reinforce the need for greater recognition of their cultural landscapes above all, by the communities themselves (marked by the resistance of identity and cultural character), and especially of women and in their continuous reaffirmation of Afro-Brazilian and Afro-descendant identities or as institutionalized 'chancellaries' and/ or ‘registre’ of the Imaterial Cultural Patrimony.